2023
DOI: 10.5812/modernc-132269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nomophobia Levels and Personality Traits of Nursing Students: A Multicenter Study

Abstract: Background: Nomophobia, short for no mobile phobia, is the fear of being without a smartphone. Nomophobia is common, especially in the young population, with an increase in the use of technology in society. Objectives: This study aimed to determine the nomophobia levels of nursing students and the relationship between nomophobia and personality traits. Methods: This multicenter, descriptive, and relational study was carried out in three different universities. The students were reached via the Web-Anket applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…If the results are explained in more detail, it is found that there is a significant positive correlation between university students' openness personality trait and nomophobia levels. This finding is in parallel with the findings of the studies on the subject in the literature (Gunay Molu et al, 2023;Oz & Tortop, 2018). This result can be explained by the fact that individuals with openness have a high tendency to use new technological developments and communicate more.…”
Section: Discussionsupporting
confidence: 86%
“…If the results are explained in more detail, it is found that there is a significant positive correlation between university students' openness personality trait and nomophobia levels. This finding is in parallel with the findings of the studies on the subject in the literature (Gunay Molu et al, 2023;Oz & Tortop, 2018). This result can be explained by the fact that individuals with openness have a high tendency to use new technological developments and communicate more.…”
Section: Discussionsupporting
confidence: 86%
“…As per the obtained characterization, the category with the highest number of students falls under "moderate nomophobia", followed by "mild or low nomophobia" and "severe nomophobia". In this respect, the results are akin to those of Tuco et al [24], Gunay Molu et al [25], Vagka et al [26] and Jilisha et al [27]. It is also worth mentioning that the overall mean score on the NMP-Q indicates a moderate level of nomophobia, as reported by Ahmed [7] and Pirinçci et al [22].…”
Section: Interpretation Of the Results And Comparison With The Litera...supporting
confidence: 76%
“…It makes it possible for anyone to gain access to just about anything they could want or need and that feeds their nomophobia tendencies. However, there is limited empirical research that attempts to unleash factors that triggered smartphone users to be nomophobia (nomobile phone-phobia) and consecutively become pathological (also known as addiction or dependency) users (Molu et al, 2023). Pathological Smartphone Use (PSU) is an emerging phenomenon that needs to be implicitly understood and addressed adequately.…”
Section: Introductionmentioning
confidence: 99%